Effects of oxidative stress on viral infections: an overview - Mohammad Enamul Hoque Kayesh; Michinori Kohara; Kyoko Tsukiyama-Kohara (npj Viruses)
Abstract Viral infections can trigger increased reactive oxygen species (ROS) production and a reduced antioxidant response in the host, leading to redox stress, inflammation, apoptosis, and ultimately, cell and tissue damage, which contribute to disease development. A better understanding of how ROS contributes to viral pathogenesis is critical for the development of novel therapeutic interventions. In this review, we discuss the current knowledge on ROS production and its effects across various viral infections, including severe acute respiratory syndrome-coronavirus-2, influenza A virus, dengue virus, Zika virus, hepatitis B virus, hepatitis C virus, and human immunodeficiency virus infections, to improve future therapeutic and preventive strategies for these infections.